The Influence of Self-Esteem and Psychological Flexibility on Medical College Students' Mental Health: A Cross-Sectional Study - Guo, Jiamei; Huang, Xin; Zheng, Anhai; Chen, Wanjun; Lei, Zhongli; Tang, Chenglu; Chen, Hongyu; Ma, Hongyan; Li, Xuemei (Frontiers in Psychiatry, 2022)
Background Mental health problems has become a major public health issue among medical students. Self-esteem and psychological flexibility were important associated factors for mental health, but their relations have not been discussed in medical students. The present study aimed to assess the status of mental health problems among medical students and identified whether psychological flexibility had a mediating role in the effects of self-esteem on the top three most common psychological symptoms. Methods A total of 810 undergraduate students from 18 classes comprised in the sample. Nine dimensions of psychological symptoms was assessed by the Symptom Checklist-90-revised (SCL-90-R). Self-esteem was measured by the Self-esteem Scale (SES) and psychological flexibility was evaluated by the Acceptance and Action Questionnaire 2nd Edition (AAQ-II) and Cognitive Fusion Questionnaire (CFQ-F). Univariate analysis and logistic regression analysis were used to determine the relationship among the top three common psychological symptoms, self-esteem, psychological flexibility, and participants' characteristics. The mediating effect of psychological flexibility between self-esteem and psychological symptoms was detected by bootstrap method. Results 57.8% of the medical undergraduate students reported positive at least one of the nine psychological symptom dimensions assessed by the SCL-90-R and 13.8% of students had moderate or more severe symptoms. The symptoms of obsessive-compulsiveness, interpersonal sensitivity, and depression were the three most common psychological symptoms among the medical students. Meanwhile, self-esteem and psychological flexibility were negatively associated to the symptoms of obsessive-compulsiveness, interpersonal sensitivity, and depression. And, almost 50% effects of self-esteem on these three symptoms in medical students exert indirect effects through psychological flexibility. Conclusions Psychological distress was quite common in the Chinese medical students. The three most common psychological symptoms were successively obsessive-compulsiveness, interpersonal sensitivity, and depression. Low self-esteem and psychological inflexibility might be the risk factors for these top three symptoms, and psychological flexibility might play a mediating role in the effects of self-esteem on these psychological symptoms.